Metatheases: artificial metalloproteins for olefin metathesis. Issue 39 (22nd August 2016) - Sauer, D. F.; Gotzen, S.; Okuda, J.
Abstract : Recent advance in the design of artificial metalloproteins for olefin metathesis is presented. Abstract : The incorporation of organometallic catalyst precursors in proteins results in so-called artificial metalloenzymes. The protein structure will control activity, selectivity and stability of the organometallic site in aqueous medium and allow non-natural reactions in biological settings. Grubbs-Hoveyda type ruthenium catalysts with an N-heterocyclic carbene (NHC) as ancillary ligand, known to be active in olefin metathesis, have recently been incorporated in various proteins. An overview of these artificial metalloproteins and their potential application in olefin metathesis is given.